All-carbon electrode materials with high specific capacitance prepared by non-covalent interaction of 2, 3-dichloro-1, 4-naphthoquinone on graphene. (16th January 2023) - Yang, Yuying; Qian, Dalan; Yang, Jingyue; Xiong, Yaling; Zhang, Ziyu; Li, Zhimin; Hu, Zhongai
Graphical abstract: Highlights: A new all-carbon electrode material (2-DCTQ/RGO) is prepared. 2-DCTQ are non-covalent grafted onto the surface of RGO. The specific capacitance of 2-DCTQ/RGO can reach up to 660F g −1 at 1 A g −1 . For comparision, one asymmetric and symmetric supercapacitors are constructed. The symmetric supercapacitor shows higher energy density than the asymmetric supercapacitor. Abstract: To effectively solve the problem of the low energy density of graphene-based supercapacitors, an effective strategy is to couple graphene with organic molecules with redox reactions, multiple active sites, and good stability. Quinones have been used as electrode materials because they are widely available, cheap, and environmentally friendly. In this study, 2, 3-dichloro-1, 4-naphthoquinone (2-DCTQ) was non-covalently interacted on reduced graphene oxide (RGO) to get an all-carbon material (2-DCTQ/RGO). 2-DCTQ/RGO composites possess both the advantages of 2-DCTQ molecules (reversible Faraday reactions with multiple electron transfer) and graphene (good conductivity and large specific surface area). As a result, the specific capacitance of the single electrode can achieve 660F g −1 at 1 A/g, which is higher than most organic small molecules reported previously. In addition, an asymmetric supercapacitor (2-DCTQ/RGO//BZTQ/RGO1 ) and a symmetric supercapacitor (2-DCTQ/RGO//2-DCTQ/RGO) are assembled at the same time. The energy density of the 2-DCTQ/RGO//BZTQ/RGO1 supercapacitor can be as high as 45 Wh kg −1 at 0.91 kW kg −1, which is considerably greater than the 2-DCTQ/RGO//2-DCTQ/RGO (25 Wh kg −1 ). 50 LEDs can be lit by connecting two such devices in series. This work provides a good idea for the construction of green and all-carbon electrode materials.